AUDIT SISTEM INFORMASI AKUNTANSI SIKLUS PENGELUARAN PADA PT. LAGIO FURNITURE - Royyan Saleh (LPPM Universitas Bina Bangsa, 2023)
The rapid development of technology makes everything easier. Many companies have also benefited from this technological development. Likewise with the company's accounting system that uses information technology in the form of an accounting information system (AIS). Lagio Furniture is a company engaged in the production of furniture for the elite. Information systems are an important part in making business operations more efficient and effective, so it is important for information systems to run properly. This study aims to examine the control and enforcement actions that exist in the expenditure cycle accounting information system at PT. Lagio Furniture. The type of audit used is the audit around the computer. Then, data were collected through observation and interviews with stakeholders. The result of this research is PT. Lagio has a good Expenditure Cycle Accounting Information System. However, there are still improvements in security plan control, operational management control, and input control